AN OVERVIEW OF PALEMBANG TEACHER TRAINING STUDENTS ACADEMIC STRESS - Ilhamsyah, Fatih; Margareta, Indah; Lutfiah Amanda, Salsabila; Pratiwi, Pratiwi; Alrefi, Alrefi (Jurnal Kopendik, 2023)
Academic stress is a problem that arises when individuals experience learning pressure caused by academic demands. This academic stress condition is often experienced by students who have high academic demands, both from educational institutions and the surrounding environment. This research aims to measure the extent of academic stress experienced by students at the Faculty of Teacher Training and Education, Sriwijaya University class of 2022. The method used in this research is quantitative descriptive using a purposive sampling technique with the criteria of students experiencing academic stress. This research sampling involved 90 respondents from 14 different study programs. Based on the results of this research, it was found that the majority of respondents experienced moderate academic stress with a percentage of 68.9%, the remaining 17.8% experienced high levels of academic stress, and 13.3% experienced low levels of academic stress.